Better Students Ask More Questions.
Simplify using the laws of exponents, then evaluate ((4^4m^3)/(3^3x^2))^4 x...
1 Answer | add yours
- (n^a) * (n^b) = n^(a + b)
- (n^a) / (n^b) = n^(a - b)
- (n^a)^b = n^(a*b)
Middle School Teacher
According to the laws of exponents:
Numerator of first fraction: (4^4 * m^3)^4 = 4^16 * m^12
Denominator of first fraction: (3^3 * x^2)^4 = 3^12 * x^8
Numerator of second fraction: (3^2 * x^3)^5 = 3^10 * x^15
Denominator of second fraction: (4^3 * m)^5 = 4^15 * m^5
You can cross simplify.
4^16 / 4^15 = 4
3^10 / 3^12 = 3^-2 = 1/9
m^12 / m^5 = m^7
x^15 / x^8 = x^7
Put it all together.
4/9 * m^7 * x^7
Posted by samhouston on October 12, 2012 at 1:59 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.